Building for everyone expand your market with design practices from google's product inclusion team - Jean-Baptiste, Annie (Gildan Audio, 2020)
Establishing diverse and inclusive organizations is an economic imperative for every industry. Any business that isn't reaching a diverse market is missing out on enormous revenue potential and the opportunity to build products that suit their users' core needs. The economic "why" has been firmly established, but what about the "how'" How can business leaders adapt to our ever-more-diverse world by capturing market share and building more inclusive products for people of color, women, and other underrepresented groups' The Product Inclusion Team at Google has developed strategies to do just that.This book makes publicly available for the first time the same inclusive design process used at Google to create user-centric award-winning and profitable products. Author and Head of Product Inclusion Annie Jean-Baptiste outlines what those practices look like in industries beyond tech with fascinating case studies. Listeners will learn the key strategies and step-by-step processes for inclusive product design that limits risk and increases profitability.Building For Everyone will show you how to infuse your business processes with inclusive design. You'll learn best practices for inclusion in product design, marketing, management, leadership, and beyond, straight from the innovative Google Product Inclusion team.